Athlete and Support Staff Perceptions of Training Modalities for the Development of Surfing-Specific Manoeuvres: A Concept Mapping Approach - Rick Dann; Jonathon Headrick; Llion Roberts; Vincent Kelly; Alex Donaldson; Alec McKenzie; Steven Duhig (Journal of Coaching and Sports Science, 2024)
This study investigated the perspectives of surfers and support staff on the importance and feasibility of common surfing training modalities. The Concept Systems groupwisdomTM web platform was used to collect and analyse data from 29 participants (18 support staff and 11 surfers). The concept mapping methodology was employed due to its effectiveness in identifying context-specific factors and real-world perspectives. Participants brainstormed statements identifying training modalities that should be incorporated in training to develop surfing-specific manoeuvres. Participants then sorted statements into clusters before rating them on importance and feasibility using a 10-point scale. Twenty-nine participants brainstormed 101 statements, which the research team synthesised and condensed to 58. Following multidimensional scaling and hierarchical cluster analysis, a 4-cluster solution was identified as the most appropriate representation of the participants sorting data: education and mindset (8 statements), physical preparation (24), in-water training (13) and dry-land training (13). Mean ratings for each cluster and statement determined the education and mindset cluster as the most important (mean = 7.5) and feasible (8.1), while the dry-land training cluster was the least important (mean = 5.9), and feasible (mean =6.0). A significant difference was found (less than 0.001) between the surfers’ (mean = 6.48) and coaching staff’s (mean = 5.61) perceived importance of dry-land training. The four modalities of surfing-specific training, rated from most to least important were: education and mindset, physical preparation, in-water training and dry-land training. Support staff should factor these four key areas into training program design and consider the potential differing views when it comes to implementing dry-land training. Additionally, these findings highlight the unique environment, task and individual constraints found within surf-training and promote the integration of a constraints led approach to training designs. This study is the first to report on the perceptions of competitive surfers and should inform both research and practice regarding the design of training environments for the development of skill-based surfing-specific manoeuvres.